Organisational Baseline Study: Overview report for Ekxang CSV, La PDR (LA01) - Grant, A.; Mienmany, Soytavanh; Keophoxay, Anousith; Khodyhotha, Khamphamy; Phonevisay, S; Souvannaxayyavong, Chantha; Toummavong, Phetsamone; Chidvilaphone, Saythong; Khamkhosy, Neeny; Pavelic, Paul; Bouapao, Lilao; Thalongsengchanh, P. (2015)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) is a strategic ten-year partnership between the CGIAR and Future Earth to help thedeveloping world overcome the threats posed by a changing climate, to achieve food security, improve agriculture and livelihoods. In 2014, CCAFS South East Asia began indentifying and implementing Climate Smart Villages (CSVs). Six CSVs were selected in three countries: Vietnam, Cambodia and Lao PDR. The objectives of the CSV is to increase the adaptive capacity of small-holder famers in light of climate change effects, improve livelihoods by sustainably increasing productivity and resilience, mitigate climate change by reducing greenhouse gases (GHGs), and enhance national food security and development goals. This report highlights the results obtained from the organizational baseline study (OBS) which was conducted in the Ekxang CSV located in Phonhong District, Vientiane Province, Lao PDR, in accordance with CCAFS guidelines. The OBS will supplement the quantitative household baseline surveys and the qualitative village baseline studies also being carried out by the Lao CSV Team in Ekxang. The household and village baselines provide information on the recipient-side of services and information. Without considering the external organisations that provide services/information to communities, the picture of current conditions remains incomplete. The main objectives of the OBS are:  Understand the current status of provision of information and services at the local level that informs farmers’ decision making and livelihood strategies in response to climate change.  Gain an in depth knowledge of the current projects, long term goals and strengths of the organizations highly valued and respected by the community members.  Identify organizations for CCAFS to engage and partner with in future interventions.  Provide indicators to allow CCAFS to monitor changes in behaviours and practices of relevant local organizations over time. To gather necessary information, we interviewed organizations working in the community whose activities included: natural resources management, environment and climate change, community development, empowering civil society, agricultural production and agricultural product processing.